Microenvironment Stiffness Amplifies Post-ischemia Heart Regeneration in Response to Exogenous Extracellular Matrix Proteins in Neonatal Mice - Wang, Xinming; Pierre, Valinteshley; Senapati, Subhadip; Park, Paul S.-H.; Senyo, Samuel E. (Frontiers in Cardiovascular Medicine, 2021)
The cardiogenesis of the fetal heart is absent in juveniles and adults. Cross-transplantation of decellularized extracellular matrix (dECM) can stimulate regeneration in myocardial infarct (MI) models. We have previously shown that dECM and tissue stiffness have cooperative regulation of heart regeneration in transiently regenerative day 1 neonatal mice. To investigate underlying mechanisms of mechano-signaling and dECM, we pharmacologically altered heart stiffness and administered dECM hydrogels in non-regenerative mice after MI. The dECM combined with softening exhibits preserved cardiac function, LV geometry, increased cardiomyocyte mitosis and lowered fibrosis while stiffening further aggravated ischemic damage. Transcriptome analysis identified a protein in cardiomyocytes, CLCA2, confirmed to be upregulated after MI and downregulated by dECM in a mechanosensitive manner. Synthetic knock-down of CLCA2 expression induced mitosis in primary rat cardiomyocytes in the dish. Together, our results indicate that therapeutic efficacy of extracellular molecules for heart regeneration can be modulated by heart microenvironment stiffness in vivo.